Biogenic silver nanoparticles produced by Trichoderma reesei inhibit SARS-CoV-2 infection, reduce lung viral load and ameliorate acute pulmonary inflammation - Marcus V.M.V. Amaral; Cláudia B. Carraro; Amanda C.C. Antoniêto; Mariana N. Costa; Thais F.C. Fraga-Silva; Ualter G. Cipriano; Rodrigo P.F. Abuná; Tamara S. Rodrigues; Ronaldo B. Martins; Andreia M. Luzenti; Glaucia R. Caruso; Priscyla D. Marcato; et al. (Current Research in Biotechnology)
The COVID-19 pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), posed a significant global health challenge and still demands efforts to develop new therapies. In this study, we investigated the potential of biogenic silver nanoparticles (AgNPs) synthesized by the fungus Trichoderma reesei to combat SARS-CoV-2 infection. In silico studies showed that AgNPs, ranging from 7 nm to 50 nm, have high affinity for spike protein from different variant of SARS-CoV-2. Our findings show that AgNPs effectively do not affect cell viability in Calu-3 cells, inhibit viral infection in Vero-E6 cells and progression of infection in vitro. Additionally, AgNPs impair caspase-1 activation, lactate dehydrogenase release and IL-1β production by human monocytes. Moreover, our study reveals that AgNPs treatment significantly alleviated acute lung injury induced by SARS-CoV-2 infection in Syrian hamsters. This suggests that AgNPs treatment effectively impairs viral replication or propagation within lung tissue, highlighting its potential as an antiviral agent against SARS-CoV-2. Further investigations are warranted to elucidate the underlying mechanisms of action of AgNPs and to assess their safety and efficacy in clinical settings. Nonetheless, our findings offer promising insights into the development of novel therapeutic strategies for combating COVID-19 and reducing its associated morbidity and mortality.